2015
DOI: 10.1002/chem.201500148
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Dehydrogenation of N‐Heterocycles Using a Carbon Nanotube–Rhodium Nanohybrid

Abstract: Rhodium nanoparticles were anchored on carbon nanotubes and the resulting nanohybrid was studied as co-catalyst, along with tert-butylcatechol, for the dehydrogenation of various N-heterocycles. The co-catalytic system operates in high yields, under the mildest conditions reported so far, and can be applied to a wide variety of secondary amine-containing scaffolds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(49 citation statements)
references
References 43 publications
1
46
0
2
Order By: Relevance
“…122 Since poor activity was observed upon replacing Q4 red with 2-tert-butylhydroquinone (TBHQ), they believed the catalytic activity of hydroquinone was affected by the geometrical effects of the substituent groups, and proposed the addition−elimination mechanism was preferred in this system.…”
Section: Scheme 41 Proposed Reaction Mechanisms Mediated By Q4 Red /Pmentioning
confidence: 99%
“…122 Since poor activity was observed upon replacing Q4 red with 2-tert-butylhydroquinone (TBHQ), they believed the catalytic activity of hydroquinone was affected by the geometrical effects of the substituent groups, and proposed the addition−elimination mechanism was preferred in this system.…”
Section: Scheme 41 Proposed Reaction Mechanisms Mediated By Q4 Red /Pmentioning
confidence: 99%
“…Similar reactivity was reported recently by Doris and coworkers, who showed that Rh nanoparticles supported on carbon nanotubes (Rh-CNT) are efficient co-catalysts with 4- tert -butyl- o -quinone in the aerobic dehydrogenations of N -heterocycles. [115] …”
Section: Bioinspired O-quinone-catalyzed Oxidation Of Aminesmentioning
confidence: 99%
“…The same research groups have reported another nanocatalyst in which Au NPs have been replaced by rhodium nanoparticles, 85‐Rh , and also this material showed a high versatility being able to promote selective aerobic mild oxidative processes on different classes of substrates such as hydroquinones, hydroxy‐lamines, silanes, hydrazines and thiols at room temperature . Nanohybrid 85‐Rh efficiently worked in the direct and co‐catalytic oxidation of hydroxylamines to the corresponding nitrones, being the catalytic system recycled 3 times and, along with tert ‐butylcatechol, in the cooperative dehydrogenation of several N ‐heterocycles and secondary amines …”
Section: Carbon Nanotubes‐based Catalystsmentioning
confidence: 99%